Effects of Melatonin and Epiphyseal Proteins on Fluoride-Induced Adverse Changes in Antioxidant Status of Heart, Liver, and Kidney of Rats - Vijay K. Bharti; R. S. Srivastava; H. Kumar; S. Bag; A. C. Majumdar; G. Singh; S. R. Pandi-Perumal; Gregory M. Brown (Advances in Pharmacological Sciences)
Several experimental and clinical reports indicated the oxidative stress-mediated adverse changes in vital organs of human and animal in fluoride (F) toxicity. Therefore, the present study was undertaken to evaluate the therapeutic effect of buffalo (Bubalus bubalis) epiphyseal (pineal) proteins (BEP) and melatonin (MEL) against F-induced oxidative stress in heart, liver, and kidney of experimental adult female rats. To accomplish this experimental objective, twenty-four adult female Wistar rats (123–143 g body weights) were divided into four groups, namely, control, F, F + BEP, and F + MEL and were administered sodium fluoride (NaF, 150 ppm elemental F in drinking water), MEL (10 mg/kg BW, i.p.), and BEP (100 µg/kg BW, i.p.) for 28 days. There were significantly P<0.05 high levels of lipid peroxidation and catalase and low levels of reduced glutathione, superoxide dismutase, glutathione reductase, and glutathione peroxidase in cardiac, hepatic, and renal tissues of F-treated rats. Administration of BEP and MEL in F-treated rats, however, significantly P<0.05 attenuated these adverse changes in all the target components of antioxidant defense system of cardiac, hepatic, and renal tissues. The present data suggest that F can induce oxidative stress in liver, heart, and kidney of female rats which may be a mechanism in F toxicity and these adverse effects can be ameliorated by buffalo (Bubalus bubalis) epiphyseal proteins and melatonin by upregulation of antioxidant defense system of heart, liver, and kidney of rats.